Dynamics of inland saline ground water and associated growth potential of common carp Cyprinus carpio for a sustainable aquaculture - P. S. Nagaraja; V. Susitharan; Siddhant Shivaji Upaskar; Jay Prakash Yadav; Pankaj Kumar; Sreedharan Krishnan; A. M. Babitha Rani; Ashok Kumar; Satyendra Singh; Dhalongsaih Reang; Sunil Kumar Nayak; Mohammad Aklakur; et al. (Discover Sustainability)
Abstract Natural and anthropogenic causes have led to soil degradation, salinisation of inland areas, and groundwater. The degraded soils are unsuitable for primary agriculture, but can be utilised for saline aquaculture. ICAR-CIFE has initiated a selective breeding program for faster growth in common carp cultured at low salinity (6–8 ppt). The present study demonstrates the dynamic nature of physico-chemical parameters of Inland Saline Ground Water (ISGW) and the growth potential of selectively bred F1 generation of common carp using ISGW. About 1560 common carp fingerlings were stocked in two ponds, each representing a unique size class (> 100 g and < 100 g). "The water quality parameters, viz., temperature, salinity, pH, dissolved oxygen, total hardness, total alkalinity, calcium, and magnesium recorded during the culture period had mean values of 30.27 ℃, 6.73 ppt, 8.48, 5.02 mg L−1, 1544.83 mg L−1, 217.29 mg L−1, 177.22 mg L−1 and 332.33 mg L−1, respectively". The average body weight of common carp at stocking in Pond 1 and Pond 2 was 42.43 g and 180.86 g, respectively. The average standard length at stocking for Pond 1 and Pond 2 was 10.57 cm and 16.57 cm, respectively. The overall means for harvest body weight and standard length at 200 days of culture in summer months were 432.48 ± 4.14 g and 22.72 ± 3.04 cm, respectively. The effects of standard length, sex of fish, and sex by pond interaction were found to be significant on the harvest body weight. The Feed Conversion Ratio (FCR), Feed Conversion Efficiency (FCE), and Protein Efficiency Ratio (PER) obtained for Pond 1 and Pond 2 were 2.19, 45.8, 1.53; 2.25, 44.44, and 1.48, respectively. The daily weight gain for Pond 1 and Pond 2 was 1.58 g and 1.61 g, respectively. In conclusion, the common carp reared in an inland saline environment showed a similar growth pattern in both size classes as reported in freshwater culture. Thus, the present study recommends common carp as a potential candidate species for inland saline aquaculture in degraded soils and advocates its scientific propagation.